Incidência de obesidade e sua relação com sedentarismo em frequentadores de clubes recreativos da cidade de Franca - Souza, Daniel Gottardo de (2010)
In the last three decades, a great number of researches has been accomplished with objective of investigating relative subjects to the obesity: if it is or not a disease, what is it different possible causes of growth and how to prevent this disease, which the best way to measure and classify, as well as that consequences can bring. This issues are because the obesity is considered, in these days, a problem of public health, mainly in the industrialized countries. There are many causes associated to the obesity and psicossocial issues (retirement and emotional disturbances), and, from the biological point of view, with several metabolic problems, among others. The increase of numbers of obesity has been explained by many factors such as sedentary life style and changes in the patterns of food consumption, for instance, larger ingestion of food and high energy density. The present study had as objective investigates the incidence of the obesity and the relationship with the sedentary style in visitors of recreational socials clubs of the city of Franca-SP. They, participated of the study 64 individuals with age between 20 and 50 years (35,3 ± 9,7), visitors and associated for leisure, recreational sports, fitness and dance. The individuals answered an International Questionnaire of Physical Activity (IPAQ - version 8) and they were also submitted to an anthropometric evaluation; it was collected the values of the weight (kg) and height (m) and calculated the Index of Corporal Mass (IMC). The individuals were divided in two different groups: active group (GA) and I sedentary group (GS). The GA had significantly lower IMC compared to GS. The values of weekly physical activity, the GA values were significantly higher compared to GS. We conclude that physically active individuals present a different level (lower) of obesity and incidence of cardiovascular and metabolic diseases if compared to sedentary individuals.